Sensing intracellular calcium ions using a manganese-based MRI contrast agent - Ali Barandov (Nature Portfolio, 2019)
There are only few MRI-compatible calcium reporters and they are limited to measuring extracellular calcium levels. Here the authors develop and validate a cell-permeable, manganese-based paramagnetic MRI contrast agent that enables monitoring intracellular calcium signals in vivo in the rat brain.